Minimally invasive veneers: current state of the art - Vanlıoğlu BA; Kulak-Özkan Y (Dove Medical Press, 2014)
Burçin Akoğlu Vanlioğlu, Yasemin Kulak-Özkan University of Marmara, Department of Prosthetic Dentistry, Istanbul, TurkeyAbstract: Ceramic veneers are considered a conservative solution for patients requiring improvement of the shape, color, or position of their anterior teeth. Ceramic veneers have been extensively and successfully used to mask intrinsic staining, to give the appearance of straightening, and to correct minor malformations of anterior teeth without the removal of substantial amounts of sound tooth substance. The current literature was reviewed to search for the most important parameters determining the long-term success and correct application of ceramic veneers. Keywords: ceramic veneers, esthetic treatment